GOVERNANSI PUBLIK DALAM PENGELOLAAN BADAN USAHA MILIK DESA DI KABUPATEN BANYUMAS - Wijaya, Shadu Satwika; Sutikno, Chamid (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
Increasing local potential is an important aspect to improve local competitiveness. Therefore, the establishment of Village-Owned Enterprises (BUMDes) is one model of village financial capacity utilization to utilize the potential and needs of the village. However, in the course of its implementation the BUMDes still found problems in achieving the objectives of using the village's potential and needs. The purpose of this study is to find the right approach in supporting efforts to improve the performance of BUMDes in managing village potential. The results of the study show that the management of the BUMDes has not been based on the needs analysis and mapping of the potential of the local village. Management of BUMDes needs to be directed towards optimizing the role of stakeholders through a governance approach.